Characteristics of gut microbiota and metabolites in extrahepatic cholangiocarcinoma and their prognostic value for resectable lesions - Ye, Cheng; Zhang, Bo; Lin, Yanyan; Han, Fangfang; Shi, Huaqing; Dong, Chunlu; Zhou, Wence (Frontiers in Cellular and Infection Microbiology, 2025)
This study aimed to investigate the relationship between gut microbiota composition, fecal metabolites, and postoperative prognosis in patients with extrahepatic cholangiocarcinoma (eCCA). A total of 53 patients with resectable eCCA and 21 healthy volunteers as a control group were included. 16S rRNA gene sequencing and metabolomic analyses revealed significant differences in the gut microbial community structure and altered fecal metabolites profiles between eCCA patients and healthy controls. Univariate and multivariate Cox regression analyses indicated that factors such as preoperative total bilirubin, indirect bilirubin, and specific metabolites were closely associated with overall survival in patients with eCCA post-surgery. The constructed nomogram model further demonstrated the predictive value of these factors, achieving a C-index of 0.718, with calibration curves confirming its strong predictive performance. In conclusion, gut microbiota composition and fecal metabolites play a crucial role in the surgical prognosis of eCCA patients, providing new insights for clinical prognostic assessment.